Uji Aktivitas Antijamur Ekstrak Etanol Daun Dadap Serep (Erythrina subumbrans (Hassk.) Merr) terhadap Trichophyton mentagrophytes dan Malassezia furfur - Revi Eluvia Zahra; Lanny Mulqie; Siti Hazar (UNISBA Press, 2024)
Abstract. The efficacy of dadap serep (Erythrina subumbrans (Hassk.) Merr) leaves is shown by the presence of secondary metabolite compounds that are very potential so that they can be used as natural antifungals. The results of phytochemical screening of ethanol extracts of dadap serep leaves showed the presence of alkaloid compounds, flavonoids, saponins and tannins that have antimicrobial activity. The purpose of this study was to determine the antifungal activity of dadap leaf extract against Trichophyton mentagrophytes and Malassezia furfur. This study used agar diffusion method with variation of concentration of ethanol extract of dadap serep leaves 50%; 25%; 20%; 15%; 10% and 5%. Comparator used ketoconazole and DMSO solvent control. Antifungal activity test parameters are indicated by the presence of inhibition zone characterized by the presence of clear zone around the punctures. The diameter of the inhibition zone formed against the fungus Trichophyton mentagrophytes with a concentration variation of 50%; 25%; 20%; 15%; 10% and 5% was 5.50 mm; 5.37 mm; 5.33 mm; 3.81 mm; 2.47 mm; 1.94 mm. While the diameter of the inhibition zone formed against Malassezia furfur fungus was 5.68 mm; 4.45 mm; 4.01 mm; 3.91 mm; 2.89 mm; 1.77 mm. Abstrak. Khasiat daun dadap serep (Erythrina subumbrans (Hassk.) Merr) ditunjukan dengan adanya senyawa metabolit sekunder yang sangat potensial sehingga dapat digunakan sebagai antijamur alami. Hasil skrining fitokimia dari ekstrak etanol daun dadap serep menunjukkan adanya kandungan senyawa alkaloid, flavonoid, saponin, dan tanin yang memiliki aktivitas antimikroba. Tujuan penelitian ini untuk mengetahui aktivitas antijamur ekstrak daun dadap serep terhadap jamur Trichophyton mentagrophytes dan Malassezia furfur. Penelitian ini dengan metode difusi agar cara sumuran dengan variasi konsentrasi ekstrak etanol daun dadap serep 50%; 25%; 20%; 15%; 10% dan 5%. Pembanding yang digunakan ketokonazol dan kontrol pelarut DMSO. Parameter pengujian aktivitas antijamur ditunjukan dengan adanya zona hambat yang ditandai dengan adanya zona bening disekitar sumuran. Diameter zona hambat yang terbentuk terhadap jamur Trichophyton mentagrophytes dengan variasi kosentrasi 50%; 25%; 20%; 15%; 10% dan 5% sebesar 5,50 mm; 5,37 mm; 5,33 mm; 3,81 mm; 2,47 mm; 1,94 mm. Sedangkan diameter zona hambat yang terbentuk terhadap jamur Malassezia furfur sebesar 5,68 mm; 4,45 mm; 4,01 mm; 3,91 mm; 2,89 mm; 1,77 mm.